Pertarungan Hukum dan Kekuasaan: Bagaimana Gagasan Wilayat al-Faqih Imam Khomeini Mendamaikan Agama dan Negara? - Mustopa, Mustopa; Bisri, Hasan (Jurnal Hukum Islam, 2024)
The conflict between law and authority is a tangible issue experienced by numerous nations globally. The law is frequently employed to serve the interests of those in power. Conversely, authority is frequently abused under the guise of law enforcement. This article seeks to elucidate Imam Khomeini’s perspectives on the conflict between law and authority. This research uses a normative legal method by utilizing primary and secondary library sources. Primary literature pertains to Khomeini’s works and texts concerning the concept of wilāyat al-faqīh. Secondary literature pertains to many writings relevant to Khomeini’s ideas and the notion of wilāyat al-faqīh. This study concludes that, according to Khomeini, the relationship between law and power is established within the context of the interaction between religion and state. Khomeini aims to actualize the notion of reconciling legal and state power within the context of religion and the people through the principle of wilāyat al-faqīh. Khomeini’s idea integrates democratic elements with religious doctrines, termed ‘theo-democracy’, nomo-democracy, or religious democracy.